First Detection of Alphacoronavirus in Bats from the World’s Largest Wetland, the Pantanal, Brazil - Tayane B. S. Magalhães; Amanda de O. Viana; Thiago B. F. Semedo; Juliane S. Saldanha; Nicole A. dos Reis; Nathalia de A. Pereira; Rachel V. P. de Barros; Hannah R. Miranda; Gabriella C. Almeida; Desyrée Y. S. R. Ozaki; Giovana S. Caleiro; Gustavo O. Fenner; et al. (Pathogens)
Coronaviruses (CoV) infect a wide variety of hosts, causing epidemics in humans, birds, and mammals over the years. Bats (order Chiroptera) are one of the natural hosts of the Coronaviridae family. They represent 40% of the total number of mammal species in the Pantanal, a biodiversity hotspot in South America. Given the recent SARS-CoV-2 pandemic, we investigated the presence of CoV in bats captured in the Brazilian Pantanal. Oral and rectal swabs collected in 2021 from 419 bats were analyzed using Pancoronavirus-nested PCR targeting the RNA-dependent RNA-polymerase (RdRp) gene. Orthocoronavirinae was detected in 16.7% (70/419) of the bats; nine samples were sequenced, confirming that Carollia perspicillata (4), Phyllostomus hastatus (2), Desmodus rotundus (1), Molossus rufus (1), and Myotis cf. nigricans (1) collected in buildings formally used by humans were infected by Alphacoronavirus genera. This is the first description of Alphacoronavirus in bats from the Pantanal. As they are natural reservoirs of CoVs, constant monitoring of bats is important to comprehend the epidemiology of emerging viruses, especially in the Pantanal biome.